2007
DOI: 10.1590/s0004-282x2007001000005
|View full text |Cite
|
Sign up to set email alerts
|

Teachers perception about epilepsy

Abstract: -Purpose: To identify in a town of Brazil the knowledge, attitude and perception of epilepsy in teachers of elementary schools and to compare these before and after a training exerc i s e . M e t h o d s :Teachers of nine public schools of Barão Geraldo, Campinas, Brazil completed a questionnaire. Tw o researchers had meetings with teachers, presenting the Global Campaign "Epilepsy out of the shadows", when the questionnaire was first completed by all attendees. Twenty teachers of these schools were motivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
0
17
0
3
Order By: Relevance
“…39 Similarly number of secondary level teacher were 76 and out of them 38.2% have poor knowledge, whereas on similar study carried out among 269 school teachers randomly selected from various secondary schools in Osogbo, the Osun State capital in South-West Nigeria, about 70% of the teachers reported their general knowledge of epilepsy is lower than half of total score. 40 A survey conducted among one hundred teachers of nine public schools of Brazil, 20% accepted that they had a poor knowledge regarding epilepsy, 41 where as in our study it is very high (47.9%). Large number of poor knowledge regarding epilepsy in Nepal is due to less public health awareness program with focus on epilepsy and least number of teachers training program on Health Education.…”
Section: Discussionmentioning
confidence: 44%
“…39 Similarly number of secondary level teacher were 76 and out of them 38.2% have poor knowledge, whereas on similar study carried out among 269 school teachers randomly selected from various secondary schools in Osogbo, the Osun State capital in South-West Nigeria, about 70% of the teachers reported their general knowledge of epilepsy is lower than half of total score. 40 A survey conducted among one hundred teachers of nine public schools of Brazil, 20% accepted that they had a poor knowledge regarding epilepsy, 41 where as in our study it is very high (47.9%). Large number of poor knowledge regarding epilepsy in Nepal is due to less public health awareness program with focus on epilepsy and least number of teachers training program on Health Education.…”
Section: Discussionmentioning
confidence: 44%
“…Almost all workers recognized that epilepsy was noncontagious and required long-term treatment, and that good treatments were available; however, only two thirds recognized epilepsy as a disorder of the brain. Similarly, Fernandes et al [ 43 ] found that a formal educational program could increase knowledge and improve attitudes among school teachers toward their pupils with epilepsy. Despite these encouraging fi ndings, the possibility persists that such infl uential others could act as what has been referred to as "stigma coaches."…”
Section: Recent Studies Of Public Attitudes Toward Epilepsymentioning
confidence: 95%
“…The studies of the attitudes of members of the general public discussed here originate from Brazil, Canada, Laos, Pakistan, Turkey, and Zambia. In Brazil, a study examined attitudes held by members of the public [ 41 , 42 ], teachers [ 43 ], and secondary school students [ 44 ]. To undertake this program, a new scale was developed and validated.…”
Section: Recent Studies Of Public Attitudes Toward Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…The training courses were divided into three modules, for health professionals; trainers (a rticle 2: Training the trainers and disseminating inform a t i o n : a strategy to educate health professionals on epileps y 1 4 -and a rticle 3: Training medical students to i m p rove the management of people with epilepsy 1 5 ) and teachers (a rticle 4: Teachers perception about epilepsy 16 ). The health professional training courses p romote confidence in dealing with patients with e p i l e p s y, better knowledge about the condition, fewer wrong beliefs and myths about epilepsy, more knowledge about dealing with AEDs and less referral to neurologists.…”
Section: Phase 2 -Training Coursesmentioning
confidence: 99%